PELATIHAN PIJAT BAYI SEBAGAI BENTUK STIMULASI TUMBUH KEMBANG BAYI BALITA BAGI KADER POSYANDU DESA TELLUMPOCCOE MAROS - Nurlina Akbar; Halida Thamrin (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Children's health is always concern because this group is vulnerable to health problems on their golden period. The involvement of parents, especially mothers and health workers, is needed. The Health Profile of South Sulawesi shows that the percentage of underweight children under five in Kabupaten Maros is ranked 4th with 8.23%. Data from interviews with the Tellumpoccoe Midwife in Kab. Maros, the number of infants under five until December 2021 is 96 toddlers and 5 health service assistent. This number shows that the ratio of health service assistent to the number of infants under five is sufficient so they should be able to assist mothers of infants under five in monitoring and stimulating growth and development. There is one way to stimulate growth and development is with baby massage which is known to be effective for increasing appetite and improving blood circulation. Health service assistent in this village have never been provided with baby massage skills, so the purpose of this community service is sharing information and baby massage skills to them. The service method includes the preparation stage, coordinating with the local government, pretest, the implementation stage, socialization and training and posttest as the evaluation stage. During the socialization and training, the health service assistant had great enthusiasm while listening to the explanation of baby massage, were active in discussing and practicing baby massage so that their knowledge and understanding increased and the five of them were able to practice good and correct baby massage